Adding A Structured Educational Session to the Rehabilitation Program of Soccer Players Following Anterior Cruciate Ligament Reconstruction: A Feasibility Study - ABDULLAH ALMUHAYA; ALI ALBARRATI; AHMED ALHOWIMEL; FARIS ALODAIBI (North American Sports Medicine Institute, 2023)
# Background While a lack of psychological preparedness and fear of movement may be linked with the anterior cruciate ligament (ACL) re-injury, these variables are rarely addressed throughout the therapy stages via educational sessions. Unfortunately, in terms of reducing fear, increasing function, and returning to play, no research has been done yet on the efficacy of adding organized educational sessions to the rehabilitation programs of soccer players post-ACL reconstruction (ACLR). Therefore, the study's aim was to assess the feasibility and acceptability of adding organized educational sessions to the rehabilitation programs post-ACLR. # Methods A feasibility randomized controlled trial (RCT) was conducted in a specialized sports rehabilitation center. Participants post ACL reconstruction were randomized to either usual care with a structured educational session (intervention group) or usual care alone (control group). This feasibility study investigated three aspects: recruitment, intervention acceptability and randomization, and retention. The outcome measures included Tampa Scale of Kinesiophobia, ACL-Return to Sport after Injury, and International Knee Documentation Committee for knee function. Measurements were done at baseline and one week after the intervention. # Results All of the 36 players who were undergoing rehabilitation post-ACLR at the center at the time of the study were invited to participate in the study. Thirty-five players (97.2%) agreed to participate in the study. The participants responded to some questions about the acceptability of the intervention and randomization and most of them thought they were appropriate. 30 (85.7%) participants completed the follow-up questionnaires one week after the randomization. # Conclusion This feasibility research found that adding a structured educational session to the rehabilitation program for soccer players after ACLR is feasible and acceptable. Full-scale RCTs with longer follow-ups and multiple locations are recommended.